Peristaltic pumping of Ellis fluid through a flexible tube with complete slip effects - Saravana, R.; Sreenadh, S.; Kumar, P. Rajesh; Babu, V. Ramesh (Journal of Naval Architecture and Marine Engineering, 2020)
The paper investigates the role of complete velocity slip on the axisymmetric peristaltic transport of Ellis fluid through a uniform flexible tube considering the long wavelength and tiny Reynolds number assumptions. The equations governing the axisymmetric flow are solved and provided the analytical expressions for axial velocity, stream function, pressure difference for shear thickening and shear thinning fluids and the effect of emerging parameters on the pressure rise with time averaged flux and stream line patterns have been discussed graphically. The trapping phenomenon results showed that the size of trapping bolus enhances with increasing values of first and second slip parameters.